2021
DOI: 10.1039/d1ee00594d
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate reduction to ammonium: from CuO defect engineering to waste NOx-to-NH3economic feasibility

Abstract: Critical to the feasibility of electrochemical reduction of waste NOx (NOxRR), as a sustainable pathway and to close the NOx cycle for the emerging NH3 economy, is the requirement of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
205
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(207 citation statements)
references
References 43 publications
1
205
1
Order By: Relevance
“…The vacancies/defects in the electrocatalysts are often reported to enhance the performance due to the increase in electronic conductivity and/or reduction in the binding energy for reactants or intermediates on the surface of the electrocatalysts. [178,191,192] However, the effect of the vacancies in photocatalysts is the subject of ongoing discussions. While some studies show that the catalytic activities of a photocatalyst are improved with the generation of the defects/vacancies, [183,[193][194][195][196][197] other reports demonstrate the culprit of the vacancies as they could be potential recombination sites for photoexcited carriers.…”
Section: (Photo)electrochemical Water Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…The vacancies/defects in the electrocatalysts are often reported to enhance the performance due to the increase in electronic conductivity and/or reduction in the binding energy for reactants or intermediates on the surface of the electrocatalysts. [178,191,192] However, the effect of the vacancies in photocatalysts is the subject of ongoing discussions. While some studies show that the catalytic activities of a photocatalyst are improved with the generation of the defects/vacancies, [183,[193][194][195][196][197] other reports demonstrate the culprit of the vacancies as they could be potential recombination sites for photoexcited carriers.…”
Section: (Photo)electrochemical Water Splittingmentioning
confidence: 99%
“…Catalyst properties such as morphology, phase arrangement, chemical compositions, or defects are among the important factors that could be correlated to the activity and selectivity of the relatively new research fields. For example, a preliminary study has shown that a mild plasma‐treatment of flame‐made CuO nanomaterials created oxygen vacancies/defects, [ 192 ] which were strongly correlated to the high activity and durability for NO x RR, achieving a NH 4 + yield of 520 µmol cm −2 h −1 at a cell voltage of 2.2 V within a flow electrolyzer. Moreover, the knowledge gained from the adaptation of flame‐made (photo)electrocatalysts for hydrogen production and CO 2 RR such as morphology‐driven activity or direct electrode assembly could be then potentially applied to other processes.…”
Section: Challenges and Opportunities Of Fspmentioning
confidence: 99%
“…Moreover, Cu-based materials have attracted increasing attention for reduction of nitrate due to additional advantages, for instance, low cost compared with other noble metals. For example, Cu/Cu-Mn 3 O 4 /Cu foam, 20 defective CuO, 21 CuO nanowire arrays, 22 Cu nanosheets, 23 and three-dimensional Cu nanobelts were applied as the cathodes for nitrate reduction. 13 However, high selectivity and faradaic efficiency for ammonia were generally achieved on the above materials, as well as extra addition of Cl − usually being required to obtain high selectivity towards N 2 .…”
mentioning
confidence: 99%
“…Recently, it has been reported by a few theoretical and experimental studies that OVs defects in CuO decreases the absorption energy for NO3reactants. On the other hand, Cu metal increases the selectivity for NH3 formation as it can bind with * NO, while no binding affinity is observed for * H species 93,94 .…”
Section: Materials Designing For Boosting Photocatalytic Nitrogen Fixationmentioning
confidence: 98%